DTC Linearization via Mismatch-Noise Cancellation for Digital Fractional-N PLLs - Helal, Eslam; Eissa, Amr I.; Galton, Ian (IEEE transactions on circuits and systems. I, Regular papers, 2022)
Digital-to-time converter (DTC) based quantization noise cancellation (QNC) has recently been shown to enable excellent fractional- N PLL performance, but it requires a highly-linear DTC. Known DTC linearization strategies include analog-domain techniques which involve performance tradeoffs and digital predistortion techniques which converge slowly relative to typical required PLL settling times. Alternatively, a DTC implemented as a cascade of 1-bit DTC stages can be made highly linear without special techniques, but such DTCs typically introduce excessive error from component mismatches which has so far hindered their use in low-jitter PLLs. This paper presents a background calibration technique that addresses this issue by adaptively canceling error from DTC component mismatches. The technique is entirely digital, is compatible with a large class of digital fractional- N PLLs, and has at least an order of magnitude lower convergence time than the above-mentioned predistortion techniques. The paper presents a rigorous theoretical analysis closely supported by simulation results which quantifies the calibration technique's convergence time and noise performance.